2020
DOI: 10.1039/d0cp02121k
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing anharmonicity and mode-coupling from matrix effects in the IR spectra of matrix-isolated carbon dioxide and methane

Abstract: A combined experimental and computational approach revealed similarities and differences in the vibrational signature of matrix-isolated carbon dioxide and methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 130 publications
1
18
0
Order By: Relevance
“…To simplify the procedure for the reduction of CO 2 methanation catalysts, the activation of Ni-Al 2 O 3 -SSC and NIAP-07-01 catalysts in a flow of reaction mixture (H 2 :CO 2 :Ar = 16:4:80) was studied. Since CO 2 and CH 4 have characteristic absorption bands [63] a qualitative assessment of the nickel reduction with varying the temperature of activation was performed by FTIR spectroscopy.…”
Section: Nio + H2 → Ni + H2omentioning
confidence: 99%
“…To simplify the procedure for the reduction of CO 2 methanation catalysts, the activation of Ni-Al 2 O 3 -SSC and NIAP-07-01 catalysts in a flow of reaction mixture (H 2 :CO 2 :Ar = 16:4:80) was studied. Since CO 2 and CH 4 have characteristic absorption bands [63] a qualitative assessment of the nickel reduction with varying the temperature of activation was performed by FTIR spectroscopy.…”
Section: Nio + H2 → Ni + H2omentioning
confidence: 99%
“…We performed multiple MI-IR experiments on stable, small molecules, such as water [29], carbon dioxide, and methane [30], fluoroethane [74], methanol, and others. In all those studies, we use argon and neon as host systems and utilize various dilutions and temperature changes to learn about the influence of matrix effects.…”
Section: Case Studies On the Synergy Of Mi-ir And Vscf/ Vcimentioning
confidence: 99%
“…However, especially the history of spectral assignments of CO 2 , CH 4 , and CD 4 shows that the interpretation of their MI-IR spectra is very controversial. We have recently shown that the matrix effects for these two molecules in different host materials are far from being systematic [30] and that methane might also rotate in Ne matrices.…”
Section: Carbon Dioxide and Methane: Matrix Effects Are Not Systematicmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we investigate the IR spectrum of carbon dioxide using matrix isolation to quench rotational transitions and use anharmonic calculations to assign all observed vibrational transitions. Previously, we successfully assigned all CO 2 monomer bands, 11 where we also provided a short review of the theoretical and experimental spectroscopy of carbon dioxide and its dimer. For a detailed review on computational studies on the (CO 2 ) 2 dimer and also recent calculations we refer to Maystrovsky et al, 12 who demonstrated that variational calculations using a tailor-made potential energy surface for the dimer on explicitly correlated coupled cluster theory yield excellent results.…”
Section: Introductionmentioning
confidence: 99%